A primer on damages of cartel suppliers: Determinants, standing US vs. EU and econometric estimation - Eckart Bueren; Florian Smuda (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
While private actions for damages against price-cartels by direct and indirect customers receive much attention, it is largely unresolved to what extent other groups that are negatively affected may claim compensation. This paper focuses on probably the most important one: suppliers to a downstream sellers' cartel. The paper shows graphically and analytically that cartel suppliers are negatively affected by the conspiracy depending on three effects: a direct quantity, a price and a cost effect. The article then examines whether suppliers are entitled to claim ensuing losses as damages in the US and the EU, with exemplary looks at England and Germany, thereby delineating the boundaries of the right to damages in different legal systems. We find that, while the majority view in the US denies standing, the emerging position in the EU, considering also recent case law and the forthcoming Damages Directive, allows for approving cartel supplier damage claims. We argue that this can indeed be justified in view of the different institutional context and the goals assigned to the right to damages in the EU. The Annex complements our result that supplier damage claims are practically viable by showing how supplier damages can be estimated econometrically with an adjusted residual demand model.
Keywords: L41; K21; 330; competition policy; comparative law; private enforcement; cartels; suppliers; quantification of damages; standing